(untitled) (American & British Studies Annual, 2016)
The article examines art interactions, one of the most topical problems in literary criticism, in the form of literary-musical intermedial aspects in E. L. Doctorow’s Ragtime. Principles of intermedial analyses have been introduced into the study with the aim of identifying artistic forms, namely specific piano phonic implications, of the musical genre of ragtime within the eponymous novel. These phonic aspects of recoding correspond to the term “word music” as defined in the typology of S. P. Scher. In addition, imitations of sound can be represented by both explicit and implicit poetological techniques defined as references in W. Wolf ’s conception of “musicalized fiction.” E. Doctorow recodes figures of ragtime as complex literary forms based on organic interactions between different intermedial techniques – verbal music, word music, musical structures and techniques. In this respect, correspondences of word music to music as defined by A.Gier have also been considered in this study. The article also attempts to interpret the artistic sense of the analyzed literary-musical intermedial forms. To this end, two main lines have been defined which are connected to eternal human values as well as the writer’s intentions to reveal controversial problems of American society.